Authority in the Classical Ḥanafī School: the Emergence & Evolution of Ẓāhir al-Riwāya - Younas, Salman (Islamic law and society, 2022)
The madhhab in its classical form was an authoritative entity with substantive boundaries that established the outer limits of the school and its authoritative doctrine. The latter involved, among other things, confronting the plurality of opinions found within the school. In this essay, I will analyse the manner in which Ḥanafī jurists attempted to limit this plurality through an authorizing discourse that created a taxonomy of legal doctrine ranking different opinions present in the corpus juris of their school. Specifically, I will examine the most authoritative corpus in this taxonomy, namely ẓāhir al-riwāya, in five parts: the first part will investigate the concept of legal authority prior to ẓāhir al-riwāya; the second part will identify the earliest usage of the term ẓāhir al-riwāya; the third and fourth parts will analyse the popularization of this doctrine, its spread, and earliest theorization; the final part will briefly investigate what ẓāhir al-riwāya denoted.